Dangla-Migama and Afro-Asiatic III: Root Initial *ḅ- - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper is a new contribution to revealing the afro-asiatic heritage in the lexicon of the Dangla-Migama group of Chadic languages by means of interbranch comparison using a.o. the ancient egypto-Semitic evidence.